Water Surface and Ground Control of a Small Cross-Domain Robot Based on Fast Line-of-Sight Algorithm and Adaptive Sliding Mode Integral Barrier Control - Wang, Ke; Liu, Yong; Huang, Chengwei; Cheng, Peng (Applied sciences, 2022)
This paper focuses on the control method of small cross-domain robots (CDR) on the water surface and the ground. The maximum size of the robot is 85 cm and the weight of the robot is 6.5 kg. To solve the problem that CDRs cannot handle the lateral velocity, which leads to error in tracking the desired trajectory, a fast line of sight (FLOS) algorithm is proposed. In this method, an exponential term is introduced to plan the yaw angle, and a fast-extended state observer (FESO) is designed to observe the side slip angle without small angle assumption. The performances and working environments of CDRs are different on the ground and the water surface. Therefore, to avoid the driver saturation and putting risk, an adaptive sliding mode integral barrier control (ASMIBC) is proposed to constrain the robot state. This control method solves the constraint failure of the traditional integral barrier control (IBC) when the desired state is a constant. The gain of the sliding mode is adaptively adjusted by the error between the limit state and the actual state. In addition, the adaptive rate is designed for uncertain time-varying lumped disturbances, such as water resistance, currents and wind. Simulation results demonstrate the effectiveness of the proposed control method.